A note on Conchodytes kempi Bruce 1989 (Crustacea, Palaemonidae, Pontoniinae), with the designation of C. kempoides sp. nov. - Bruce, A. J. (Zootaxa, 2013)
Bruce (1989) reported on a pair of specimens of the pontoniine shrimp Conchodytes kempi from the Philippine Islands. These were subsequently referred to by Fransen (1994) as a junior synonym of C. biunguiculatus (Paulson), but these specimens may well represent a distinct species and deserve further examination. In general, Conchodytes species are of considerable size, with CLs of about 8.7 and 9.2 for males and females, respectively of C. biunguiculatus from the Andaman Islands and are generally found in association with larger bivalve hosts, such as Pinna and Atrina (Bruce 1989). The Philippine specimens are adult, as the female is ovigerous, but of very small size with CLs of only 2.5 and 3.75 mm. They were also found in association with a specimen of Isognomon, a host species not reported as a host for C. biunguiculatus